Perbandingan Kinerja Rangka Terbuka Dengan Dan Tanpa Pengaruh Flat Slab (Studi Kasus Gedung Transmart Pekanbaru) - Syamsul Fikri; Zulfikar Djauhari; Reni Suryanita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
A flat slab is a building structure component that uses a portal system and a plate that is directly supported by a column with or without plate thickness at the top of the column (drop panel). Flat slabs are still rarely used in the city of Pekanbaru, because there are still many conventional plates used. To determine the performance of each structural system, it is necessary to examine the influence at the flat slab and conventional plate system to the performance of the structure of the building. The purpose of this research is to identify the effect of flat slabs on the reinforced concrete open frame structure systems and comparing them with conventional structural systems. Two models were constructed, model 1 was the original Transmart Pekanbaru Building model, while model 2 replaced the flat slab on the ground floor with a 600x400 beam. The results showed that the story drift value in model 1 was very large compared to a model 2 with a comparison value of 60,00 in the direction X and 11,50 in the direction Y. Based on story drift in model 1 and model 2, the building structure has met the requirements for the story drift permit of 0.6 on the ground floor and 0.1 on the 1st to 3rd floors. So that it can be concluded that conventional systems are better than flat slabs because beam factors greatly affect the displacement of a building structure.Keywords: flat slab, conventional plate, story drift